(untitled) (Bangladesh Journal of Bioethics, 2012)
Psychotherapy is a vital component of any treatment programme in the management of psychiatric disorders. It is very essential that the therapist receives adequate training prior to embarking on therapy with patients. There are various ethical issues and boundaries that the therapist must be aware of when dealing with psychiatric patients. Both experienced and novice therapist may experience confusion and dilemma when it comes across certain boundaries for the benefit of the patients. The present article introduces the readers the various boundaries that need to be maintained in psychotherapy and how the boundary is crossing or violations can lead to serious problems. The issue of gifts, fees, transference, physical contact between therapist and patient and sexual boundary violations are discussed. The need for focusing on boundaries in psychotherapy training is stressed. DOI: http://dx.doi.org/10.3329/bioethics.v3i2.11701 Bangladesh Journal of Bioethics 2012; 3(2):16-26